1995
DOI: 10.3354/dao021163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding on the development of bacterial gill disease in rainbow trout Oncorhynchus mykiss

Abstract: Three trials were conducted to determine if feeding influenced the development of bacterial gill disease (BGD) in fingerling rainbow trout Oncorhynchus mykiss following bath exposure to Flavobacterium branchiophilum (LAB 4a). In each trial (Trial 1. n = 70 X 3; Trial 2, n = 140 X 3 ; Trial 3, n = 250 X 3), the comparison groups (fed, unfed, negative controls) were held in similar conditions and (where applicable) fed prior to exposure to the pathogen. Severe clinical signs and high rates of mortality developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…The marked lamellar hyperplasia associated with some of the more chronic BGD infections (Ostland et al 1990;Speare et al 1991a,b) that dramatically increases the diffusional distance, does not occur in the acute stages of the disease. Instead, there is mild to moderate swelling of lamellar pavement epithelium within the first 12 to 24h (MacPhee et al 1995). This could account for some increase in diffusional resistance across the gill lamellar epithelium, thereby contributing to a hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The marked lamellar hyperplasia associated with some of the more chronic BGD infections (Ostland et al 1990;Speare et al 1991a,b) that dramatically increases the diffusional distance, does not occur in the acute stages of the disease. Instead, there is mild to moderate swelling of lamellar pavement epithelium within the first 12 to 24h (MacPhee et al 1995). This could account for some increase in diffusional resistance across the gill lamellar epithelium, thereby contributing to a hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that experimental challenge of rainbow trout with F. branchiophilum causes mortality and protracted morbidity only if the fish are fed (MacPhee et al 1995). Early attempts failed to produce BGD in fish while they were in the "fish boxes" because the fish would not take feed pellets, and thus we decided to use gastric feeding tubes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, larvae are not believed to be as adept as larger fish at locating feed; therefore, it has been a common practice to overfeed hatchery fish to ensure they are receiving adequate nutrition. Overfeeding increases systemic bacterial loading, the potential for gill infections (MacPhee et al 1995), and contributes to poor water quality (Faure and Labbe 2001). Siphoning excess feed can be extremely labor intensive and introduces risks of accidental damage to the fish during the siphoning process.…”
mentioning
confidence: 99%